Pengembangan Lembar Kerja Siswa (LKS) Berbasis Pendekatan Realistic Mathematic Education (RME) Untuk Memfasilitasi Kemampuan Representasi Matematis Siswa SMP - Ranti Mustika Sari; Zubaidah Amir M.Z.; Risnawati Risnawati (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2017)
This research aimed at developing, producing a valid and practical students’ workbook Realistic Mathematic Education Approach Based and facilitating student mathematic representing ability on Systems of Linear Equations in Two Variables material.The method of this research was a Research and Development (R&D) through the development of 4-D (Define, Design, Develop, and Disseminate) Model.This research was administered at State Junior High School 2 Pasir Penyu.The subjects of this research were 29 students of class VIII 1, and the object was student mathematic workbook Realistic Mathematic Education Approach Based.The questionnaire tests of validity, practicality, and mathematic representing test. were the instruments of collecting data.It could be concluded that validity test result on student workbook Realistic Mathematic Education Approach Based on Systems of Linear Equations in Two Variables material at State Junior High School 2 Pasir Penyu was on valid category (78.21%).It proved that the developed student workbook was avowed by validators because it accomplished all components, and it was a revised product.Practicality test result by students was avowed very practical (94.16%).Student mathematic workbook Realistic Mathematic Education Approach Based successfully facilitated student mathematic representing ability with the percentage of mastery level 82.5%.The result showed that Student mathematic workbook Realistic Mathematic Education Approach Based was valid, practical, and student mathematic representing ability.